2009
DOI: 10.1002/bjs.6594
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of defunctioning stomas in low anterior resection for rectal cancer

Abstract: A defunctioning stoma decreases clinical anastomotic leak rate and reoperation rate. It is recommended after low anterior resection for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
254
1
30

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(300 citation statements)
references
References 40 publications
8
254
1
30
Order By: Relevance
“…This statement is supported by data from various randomized studies that have been subjected to meta-analysis, showing an improvement in outcome associated with protective stoma with LAR. (11,12) In our study, twelve cases of LAR with ileostomy were performed in which anastomotic leakage were present in 2(7%) cases. In one of the study, Matthiessen P et al anastomotic leakage was present in 12 (10.17%).…”
Section: Discussionmentioning
confidence: 78%
“…This statement is supported by data from various randomized studies that have been subjected to meta-analysis, showing an improvement in outcome associated with protective stoma with LAR. (11,12) In our study, twelve cases of LAR with ileostomy were performed in which anastomotic leakage were present in 2(7%) cases. In one of the study, Matthiessen P et al anastomotic leakage was present in 12 (10.17%).…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, the Dutch TME trial revealed that the presence of drain was strongly associated with a lower leak rate (9.6%) compared with those without drain (23.5%) and this significance resulted in the relative risk of 2.5 (95%CI; 1.6 to 4.1) by the multivariate analysis, favoring the use of pelvic drain in reducing the anastomotic leak rate [15]. Besides, since this study provided supportive data to the clinical decision to construct covering stoma when performing TME, the main interest of the trials on TME has been shifted to whether to create defunctioning stoma or not at the time of initial surgery [16].…”
Section: Use Of Drain and The Incidence Of Anastomotic Leakmentioning
confidence: 76%
“…В публикации K. Beirens и соавт., в которой обобщен собственный опыт лечения 1912 пациентов за 5 лет, показано досто-верное снижение частоты возникновения несостоя-тельности анастомоза с 10,2 до 4,3 % у больных со сформированными разгрузочными стомами и ле-тальности в послеоперационном периоде до уровня 0 % против 4,8 % у пациентов без стом соответствен-но [38]. Целесообразность формирования стом при низких передних резекциях прямой кишки под-тверждается и метаанализами опубликованных дан-ных [39]. С другой стороны, формирование разгрузоч-ной стомы сопряжено с рядом нежелательных явлений (в первую очередь с дегидратацией), а реконструктив-ный этап хирургического лечения может иметь свои осложнения.…”
Section: результатыunclassified